MULTIVARIATE ANALYSIS OF HEALTHCARE SYSTEMS IN SELECTED EUROPEAN UNION COUNTRIES. CLUSTER ANALYSIS. - Miszczyńska, Katarzyna (Metody Ilościowe w Badaniach Ekonomicznych, 2013)
The European Union as a whole tends to be a highly diversified entity. Therefore it should not be surprising that the main goal of EU authorities is the limitation of inequalities among member countries. The aim of this study is to identify some groups of countries from the EU that show similar characteristics concerning the functioning of healthcare sectors. The selected countries will be analysed through the prism of characteristics connected with the financial and organizational issues. The study will be backed up by a chosen multivariate statistical analysis — cluster analysis.